Designing a radio-interferometric array of Yagi-Uda antennas with spectral window centre at 400 MHz - Muñoz, íngel; Hernández, Leonardo (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
It is well known that the observation of celestial bodies through the use of radioastronomic devices has, generally speaking, important advantages in comparison to traditional studies concerning the visual spectrum. Moreover, radio-interferometry gives additional advantages to the device, such as the enhancement of the signal receptor effective area, higher gaining and better array directivity. Despite the number of experimental details, the design of a radio-telescope made up of an array of antennas whose radiation fields interfere among themselves does not involve excessive theoretical complications, in particular if Yagi-Uda antennas are used. The authors describe in this paper the designing and characteristics of a radio-interferometric array with Mills Cross symmetry, 4x4 twelve elements Yagi-Uda antennas, set to 400 MHz. Finally, the potential of the array is briefly analysed in order to be used for radio-heliographics studies.